Pola Konsumsi makanan Kariogenik Sebagai Faktor penyebab Karies Gigi pada Anak SD Negeri 5 Waai Kabupaten Maluku Tengah - Zasendy Rehena (MOLUCCAS HEALTH JOURNAL, 2020)
Dental caries in school children can cause children to experience loss of chewing power and digestion disruption, which results in disruption of children's health. This condition will certainly reduce the frequency of children's attendance to school, disrupt the concentration of learning, affect the child's appetite. One of the causes of dental caries in school children is the pattern of consumption of cariogenic foods because at this age children usually like snacks and drinks as they wish. The purpose of this study was to determine the relationship between the type and frequency of consuming cariogenic food with the incidence of dental caries in SD Negeri 5 Waai District, Central Maluku. Method This study uses a descriptive study using a cross sectional design. Sampling with a purposive sampling method. Data were analyzed using the chi square test. The results showed there was a relationship between the type and frequency of consuming cariogenic food with the incidence of dental caries in students of SD Negeri 5 Waai, Central Maluku, with avalue of ρ = 0.027 and p = 0.028 <α 0.05. The conclusion that the type and frequency of consuming cariogenic food is related to the incidence of dental caries in students of SD Negeri 5 Waai, Central Maluku Regency. It is recommended to the school to be able to seek a healthy canteen at school and counseling oral health. Also for parents to pay attention to the habit of consuming cariogenic food by elementary school children while at school or at home.Keywords: Consumption pattern; cariogenic food; dental caries